Severity of functional impairments by race and sex in older patients hospitalized with acute decompensated heart failure. Issue 12 (19th August 2022) - Ye, Fan; Nelson, M. Benjamin; Bertoni, Alain G.; Ditzenberger, Grace L.; Duncan, Pamela; Mentz, Robert J.; Reeves, Gordon; Whellan, David; Chen, Haiying; Upadhya, Bharathi; Kitzman, Dalane W.; Pastva, Amy M.
Abstract: Background: Older patients hospitalized with acute decompensated heart failure (ADHF) have marked functional impairments, which may contribute to their delayed and incomplete recovery and persistently poor outcomes. However, whether impairment severity differs by race and sex is unknown. Methods: REHAB‐HF trial participants (≥60 years) were assessed just before discharge home from ADHF hospitalization. Physical function [Short Physical Performance Battery; 6‐min walk distance (6MWD)], frailty (Fried criteria), cognition [Montreal Cognitive Assessment (MoCA)], quality‐of‐life [Kansas City Cardiomyopathy Questionnaire, Short‐Form‐12, EuroQol‐5D‐5L], and depression [Geriatric Depression Scale (GDS)] were examined by race and sex. Results: This prespecified subgroup cross‐sectional analysis included 337 older adults (52% female, 50% Black). Black participants were on average younger than White participants (70.3 ± 7.2 vs. 74.7 ± 8.3 years). After age, body mass index, ejection fraction, comorbidity, and education adjustment, and impairments were similarly common and severe across groups except: Black male and Black and White female participants had more severely impaired walking function compared with White male participants [6MWD (m) 187 ± 12, 168 ± 9170 ± 11 vs. 239 ± 9, p  < 0.001]; gait speed (m/s) (0.61 ± 0.03, 0.56 ± 0.02, 0.55 ± 0.02 vs. 0.69 ± 0.02, p  < 0.001); White female participants had the highest frailty prevalence (72% vs. 47%–51%, p  = 0.007); and Black participants had lower MoCA scores compared with White participants (20.9 ± 4.5 vs. 22.8 ± 3.9, p  < 0.001). Depressive symptoms were common overall (43% GDS ≥5), yet underrecognized clinically (18%), especially in Black male participants compared with White male participants (7% vs. 20%). Conclusion: Among older patients hospitalized for ADHF, frailty and functional impairments with high potential to jeopardize patient HF self‐management, safety, and independence were common and severe across all race and sex groups. Impairment severity was often worse in Black participant and female participant groups. Formal screening across frailty and functional domains may identify those who may require greater support and more tailored care to reduce the risk of adverse events and excess hospitalizations and death.